The Ijtihad Approach in Nahwu Reform: Amin Al-Khuli’s Thoughts on Modern Arabic Grammar - Muid, Abdul; Zenrif, M Fauzan; Yusup, Agung; Vahlepi, Sahrizal; Mahdi, Mohamad Wardougou (Fakultas Ilmu Budaya, Universitas Jambi, 2024)
This study aims to analyze the concept of ijtihad in the science of nahwu according to the view of Amin Al-Khuli, who emphasizes the need for nahwu reform to be more relevant to the needs of modern times. This study uses a textual analysis method of the work of Amin Al-Khuli Manahij Tajdid fi al-Nahwi wa al-Balaghah wa al-Tafsir wa al-Adab accompanied by a comparative study between classical Arabic linguistic theory and modern linguistic theory. The main findings in the study show that ijtihad in nahwu offers flexibility in grammar rules, so that the Arabic fusha language can remain relevant without neglecting its authenticity. In addition, although Al-Khuli emphasizes the importance of fusha as a symbol of cultural identity, there is a need to integrate the functions of local dialects in everyday communication. The implications of this study highlight the urgency of a holistic language policy to maintain the relevance of fusha in the modern social context, as well as encourage critical thinking in the development of Arabic grammar (nahwu) that is adaptive to the development of the times. Abstrak Penelitian ini bertujuan untuk menganalisis konsep ijtihad dalam ilmu nahwu menurut pandangan Amin Al-Khuli, yang menekankan perlunya reformasi nahwu agar lebih relevan dengan kebutuhan zaman modern. Penelitian ini menggunakan metode analisis tekstual terhadap karya Amin Al-Khuli Manahij Tajdid fi al-Nahwi wa al-Balaghah wa al-Tafsir wa al-Adab yang disertai dengan kajian komparatif antara teori linguistik Arab klasik dan teori linguistik modern. Temuan utama dalam penelitian menunjukkan bahwa ijtihad dalam nahwu menawarkan fleksibilitas kaidah tata bahasa, sehingga bahasa Arab fusha dapat tetap relevan tanpa mengabaikan keasliannya. Selain itu, meskipun Al-Khuli menekankan pentingnya fusha sebagai simbol identitas budaya, ada kebutuhan untuk mengintegrasikan fungsi dialek lokal dalam komunikasi sehari-hari. Implikasi dari penelitian ini menyoroti urgensi kebijakan bahasa yang holistik untuk menjaga relevansi fusha dalam konteks sosial modern, sekaligus mendorong pemikiran kritis dalam pengembangan ilmu tata bahasa Arab (nahwu) yang adaptif terhadap perkembangan zaman.